Practical approach for safe anesthesia in a COVID-19 patient scheduled for emergency laparotomy - Umesh Goneppanavar; Sameer Desai; Jasvinder Kaur; Rajesh S Phatake; Roopa Sachidananda; Ravi Bhat (Wolters Kluwer Medknow Publications, 2020)
COVID-19 patients presenting for emergency laparotomy require evaluation of surgical illness and viral disease. As these patients are likely to have a wide spectrum of deranged physiology and organ dysfunction, optimization should start preoperatively and continue through intraoperative and postoperative recovery periods along with appropriate antimicrobial cover. The goal should be not to delay damage control surgery in favor of evaluation and optimization. When a COVID-19 positive or suspected patient is to be operated for laparotomy, the situation often demands general anesthesia with invasive monitoring and analgesia complemented by regional anesthesia to minimize postoperative opioid requirements to facilitate early recovery. This particular article addresses the issues related to emergency laparotomy management in relation to COVID-19 patient. Healthcare workers should diligently use effective PPE and practice disinfection to prevent spread. Video-communication is an effective means of evaluation. Information expected from investigations should be weighed against risk of exposure to healthcare workers/laypersons. Simulation and memory aids should be used to familiarize team members with roles and techniques of management while in PPE. Step-wise detailed planning for patient transfer, anesthesia induction, maintenance and emergence, aid in enhancing HCW safety without compromising patient care.